Pemodelan Kesetimbangan Termodinamika Non-Stoikiometrik Gasifikasi Biomassa - Mazlani Mazlani; Hari Rionaldo; Zulfansyah Zulfansyah (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Biomass gasification is a technology that can be used to convert biomass into gas fuel, chemicals, and energy which is more convenient and usable. The quality of the resulting product depends on the of gasification agents such as air, steam, oxygen, and process parameters such as temperature, type of biomass, and equivalent ratio. The biomass gasification process presents the mathematical model that has been given and solve the modeling with non-stoichiometric thermodynamic equilibrium method. The non-stoichiometric thermodynamic equilibrium model involves minimizing the Gibbs free energy. This model is useful for further research if there are changes in the gasification agent and process parameters.Keywords : biomass gasification, gibbs free energy, non-stoichiometric